On the question of the relevance of Economics as a science: Postmodern filosofia critique - Emerson Abraham Jackson (Ludwig-Maximilians-Universität (LMU), 2018)
This article has adopted an open discourse in addressing pertinent concerns about the scientific existence of economics as a discipline. In doing so, some (critical) Filosofia arguments have been provided in ensuring that a well balanced approach is taken on the subject. Obviously, the approach of Popperian falsification used by economic science to address scientific justification through its varied scientific platform of technology applications like EVIEWS, STATA, MatLab and many more, have been applauded. Albeit such advances, the views of modern and postmodern critics have also come out saliently in a bid to ensuring open discourses are brought to the fore as a way of adding scientific value to the subject matter. In concluding, it was acknowledged that more is needed in ensuring that economic science as practiced by economists takes an open approach to critical discourse(s), reflecting reality about its pursed scientific ventures, given the persistence of economic volatility manifested across the global community. – – Cet article a adopté un discours ouvert sur les préoccupations pertinentes concernant les existence de l'économie en tant que discipline. Ce faisant, certains arguments (critiques) de Filosofia ont été fourni pour assurer qu'une approche bien équilibrée est prise sur le sujet. De toute évidence, le approche de la falsification popperienne utilisée par la science économique pour répondre à la justification scientifique à travers sa plate-forme scientifique variée d'applications technologiques comme EVIEWS, STATA, MatLab et beaucoup d'autres ont été applaudis. Bien que de telles avancées, les points de vue des les critiques postmodernes sont également sortis nettement dans le but de s'assurer que les discours ouverts sont portés à l'avant comme un moyen d'ajouter une valeur scientifique à la matière. En conclusion, il était reconnu que plus il est nécessaire de faire en sorte que la science économique telle que pratiquée par les économistes adopte une approche ouverte au (x) discours critique (s), reflétant la réalité au sujet de ses entreprises, compte tenu de la persistance de la volatilité économique manifestée à travers la communauté mondiale.
Additional information: Working Paper document on Critical Economics
Keywords: B5; B41; 330; Economic Science; Scientific Methodology; Filosofia; Postmodern Critique